Inferior Vena Cava Oxygen Saturation during the First Three Postnatal Days in Preterm Newborns with and without Patent Ductus Arteriosus - Ece Yapakçı; Ayşe Ecevit; Deniz Anuk İnce; Hande Gülcan; Aylin Tarcan; Mahmut Gökdemir; M. Agah Tekindal (Balkan Medical Journal, 2014)
Background: Inferior vena cava (IVC) oxygen saturation as an indicator of mixed venous oxygenation may be valuable for understanding postnatal adaptations in newborn infants. It is unknown how this parameter progresses in critically ill premature infants.